REFLEKSI NILAI HUYULA AMBU DI BALIK PRAKTIK AKUNTANSI PADA KEGIATAN PENYAMBUTAN BULAN SUCI RAMADHAN - Thalib, Mohamad Anwar; M Sahrul; Tiara, Nurahmi; Rizkah, Miftahur Rizkah; Syamsudin, Sulis Lia (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2023)
This research departs from the problem of the domination of the adoption of modern accounting, which impacts the increasingly marginalized local cultural values behind accounting practices. Meanwhile, current accounting studies still need to reveal how the accounting plays a role in everyday life, cultural implementation processions, and annual activities such as welcoming the holy month of Ramadan. This study aims to reflect on the local cultural values behind accounting practices in welcoming the holy month of Ramadan. This study uses an Islamic paradigm with an Islamic ethnomethodological approach. There are five data analysis stages: charity, knowledge, faith, revelation information, and courtesy. The results of the study show that in the activities of welcoming the holy month of Ramadan, there are accounting practices in the form of wages for residents who work together to clean and beautify the mosque, consumption costs that are voluntarily given by residents to workers, and repair costs for mosque equipment or equipment. It is broken or no longer working. The accounting practice is a condition with non-material values in the form of help. In the Islamic culture of Gorontalo, this activity is better known as huyula ambu or mutual help activities for the common good. The results of this study provide implications for the concept of accounting based on local cultural values and present an overview of how accounting plays an essential role in everyday life, especially in welcoming the holy month of Ramadan.